Ecotourism Philosophy Oriented to Local Wisdom the Integration Model of Presean and Nature Conservation in Sade Village - Khofi, Muhammad Yazid; Isdin, Isdin; Azhari, Ari (JURNAL ILMIAH DETUBUYA, 2025)
This study aims to explore the philosophy of local wisdom-based ecotourism through the integration of the Presean tradition and nature conservation in Sade Village, West Nusa Tenggara (NTB). Using a qualitative approach with an integrative literature review method, this study identifies and synthesizes theoretical and empirical findings from various academic publications retrieved through Google Scholar, Scopus, DOAJ, and Scispace databases. The results of the study indicate that Presean is not merely a cultural attraction, but also contains ecological values ​​such as balance, responsibility, and harmony with nature. These values ​​have the potential to become an ethical framework in ecotourism development that not only preserves the environment but also strengthens local cultural identity. These findings propose a conceptual model of culture-based ecotourism that is participatory, holistic, and sustainable. This model has the potential to be replicated in similar destinations with strong local wisdom. This study recommends further research to develop instruments for operationalizing cultural values ​​in tourism governance and evaluating their impact on tourist behavior. This study is expected to provide theoretical and practical contributions to the development of sustainable community-based ecotourism.